Pengaruh Model The Power Of Two Terhadap Hasil Belajar PPKN Siswa Kelas V SD Negeri 199 Palembang - Ashari, Rahman; Hetilaniar, Hetilaniar; Selegi, Susanti Faipri (Institut Teknologi Pendidikan Indonesia, 2022)
Citizenship Education is very important to be applied in elementary schools for the intelligence and personality skills of students such as physical and spiritual fitness,independence. Therefore, the difficulty that often arises is that the learning outcomes of civic education are still low. Based on this, the problem in this research is whether there is an effect of the power of two model on the learning outcomes of V-grade Civics at SD Negeri 199 Palembang. The purpose of this research is to find out whether there is an effect of the power of two model on the learning outcomes of fifth grade Civics at SD Negeri 199Palembang. Using the correct research method, the research design was posttest-only control group design. The data obtained were analyzed using t-test. Based on the t-test analysis for the final test at a significant level = 0.05, it was obtained that tcount > ttable (tcount = 15.5 > ttable = 1.67), so that there could be an effect of the two-strength model on the learning outcomes of Civics Class V SD Negeri 199 Palembang.